O sposobach definiowania znaczeń leksyki religijnej w tematycznych słownikach internetowych - Czarnecka, Katarzyna (Poznańskie Spotkania Językoznawcze, 2015)
The research material comprises dictionaries of terms related to Catholicism, functioning on Polish websites. The aim of this lexicographical-nature study is the description of dictionary definitions, namely ways of defining meanings that appear in the online dictionaries collected. The author distinguishes 3 types of texts appearing in the section of the headword, in which a definition is traditionally placed: 1) information about what the headword means, tending to be balanced, provided in stylistically neutral vocabulary, sometimes with features of academic style – objective definitions; 2) information about the meaning of a word, supplemented by a humorous or satirical presentation of the designatum – subjective definitions; 3) Texts that replace a proper definition, connected to headwords in different ways – pseudo-definitions (failed definitions or comments). The number of dictionaries published on the Internet proves that the model of a dictionary as a way to share information is considered useful and attractive. The method of composing a definition, however, shows how different objectives are attributed to online dictionaries: not only should they impart knowledge about the language, but first of all describe the world and shape favorable or reluctant attitude of readers to religious issues.